The EuroMyositis registry: an international collaborative tool to facilitate myositis research. Issue 1 (30th August 2017) - Lilleker, James B; Vencovsky, Jiri; Wang, Guochun; Wedderburn, Lucy R; Diederichsen, Louise Pyndt; Schmidt, Jens; Oakley, Paula; Benveniste, Olivier; Danieli, Maria Giovanna; Danko, Katalin; Thuy, Nguyen Thi Phuong; Vazquez-Del Mercado, Monica; et al.
Abstract : Aims: The EuroMyositis Registry facilitates collaboration across the idiopathic inflammatory myopathy (IIM) research community. This inaugural report examines pooled Registry data. Methods: Cross-sectional analysis of IIM cases from 11 countries was performed. Associations between clinical subtypes, extramuscular involvement, environmental exposures and medications were investigated. Results: Of 3067 IIM cases, 69% were female. The most common IIM subtype was dermatomyositis (DM) (31%). Smoking was more frequent in connective tissue disease overlap cases (45%, OR 1.44, 95% CI 1.09 to 1.90, p=0.012). Smoking was associated with interstitial lung disease (ILD) (OR 1.32, 95% CI 1.06 to 1.65, p=0.013), dysphagia (OR 1.43, 95% CI 1.16 to 1.77, p=0.001), malignancy ever (OR 1.78, 95% CI 1.36 to 2.33, p<0.001) and cardiac involvement (OR 2.40, 95% CI 1.60 to 3.60, p<0.001). Dysphagia occurred in 39% and cardiac involvement in 9%; either occurrence was associated with higher Health Assessment Questionnaire (HAQ) scores (adjusted OR 1.79, 95% CI 1.43 to 2.23, p<0.001). HAQ scores were also higher in inclusion body myositis cases (adjusted OR 3.85, 95% CI 2.52 to 5.90, p<0.001). Malignancy (ever) occurred in 13%, most commonly in DM (20%, OR 2.06, 95% CI 1.65 to 2.57, p<0.001). ILD occurred in 30%, most frequently in antisynthetase syndrome (71%, OR 10.7, 95% CI 8.6 to 13.4, p<0.001). Rash characteristics differed between adult-onset and juvenile-onset DM cases ('V' sign: 56% DM vs 16% juvenile-DM, OR 0.16, 95% CI 0.07 to 0.36, p<0.001). Glucocorticoids were used in 98% of cases, methotrexate in 71% and azathioprine in 51%. Conclusion: This large multicentre cohort demonstrates the importance of extramuscular involvement in patients with IIM, its association with smoking and its influence on disease severity. Our findings emphasise that IIM is a multisystem inflammatory disease and will help inform prognosis and clinical management of patients.